Foods and their components promoting gastrointestinal cancer. Issue 5 (September 2016) - Muscaritoli, Maurizio; Amabile, Maria Ida; Molfino, Alessio
Abstract : Purpose of review: Cancer represents one of the most feared diseases. Despite an increasing number of available scientific data, most people remain unaware of those basic dietary and healthy lifestyle measures, which might reduce their risk to develop cancer. Environmental factors, diet, and lifestyle play a crucial role in the development of several different neoplastic diseases, particularly gastrointestinal cancer. In this article, we aimed at focusing on foods and their components able to increase gastrointestinal cancer risk. Recent findings: During the last few years, major emphasis has been addressed on the relation between red meat and gastrointestinal cancer. Many potential mechanisms linked red meat consumption and cancer risk, including heterocyclic amines, polycyclic aromatic hydrocarbons, N-nitroso compounds, and heme iron. Other chemical substances, contaminating food, such as acrylamide, showed gastrointestinal carcinogenic properties. Summary: Correct diet and lifestyle are clinically relevant strategies in preventing gastrointestinal cancer. In the fight against cancer, nutritional educative intervention programs are necessary to spread the knowledge on healthy eating and appropriate nutrition to reduce cancer risk.